The Study of Genesis I-XI - Mitchell, T. C. (Tyndale bulletin, 1957)
Study of Genesis 1–11 requires examination of the Hebrew text, archaeology, and relevant Sumerian and Akkadian legends, leading to a synthesis consistent with a high view of Scripture.